Attitudes towards Euro-English in a European Union institution - Balič, Tina (ELOPE (Ljubljana), 2016)
This study deals with the attitudinal aspect of Euro-English, denoting a specific form of the English language that is frequently used within the institutions of the European Union. A questionnaire survey was conducted among 285 representatives who work for one of these institutions in Brussels. The respondents were asked to rate several deviations from Standard English, identified in a corpus-based analysis of EU texts, as either "acceptable" or "unacceptable" English usage. The findings reveal that the high acceptability rates of the proposed features among the non-native English-speaking respondents were mainly related to their proficiency in English and/or mother tongue interference. Moreover, since native speakers of English also accepted most of the proposed deviations, it follows that the participants did not seem to be aware of non-standardness in the test sentences. Euro-English must be regarded as EU jargon due to its technical, administrative or legal nature and not as a separate non-standard form of English for EU institutional settings.
Keywords: Corpus linguistics; evroangleščina; korpusna lingvistika; odnos do jezika; odstopanja od standardne angleščine; žargoni